An overview of current phase 3 radiopharmaceutical therapy clinical trials - Lepareur, Nicolas (Frontiers in Medicine, 2025)
Over the past few years, radiopharmaceutical therapy has emerged as a groundbreaking therapeutic modality, taking advantage of the unique properties of radionuclides to deliver molecularly targeted therapy with high precision and transforming the landscape of precision oncology and personalized medicine. Its development reflects decades of advances in nuclear medicine, chemistry, and cancer biology. However, until recently, definitive clinical evidence was lacking to establish it into treatment plans, with few large randomized controlled clinical studies. The last two decades witnessed a paradigm shift, with three successful phase 3 studies which shed light on radiopharmaceutical therapy. This paper offers a brief overview of currently active phase 3 studies to highlight the dynamism and promise of this clinical domain, as well as the large variety of cancers being treated.